ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN DAN HARGA JASA ANGKUTAN DARAT DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA PT. GUSTAMAN EXPRESS PEKANBARU - -, Muhammad Fadhil Gustaman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to see the level of customer satisfaction with the service quality and price of land transportation services at PT. Gustaman Express Pekanbaru. The population in this study are individuals or companies who have used PT delivery services. Gustaman Express since 2022, totaling 612 people or entities. The number of samples in this study was 115 people or bodies based on predetermined criteria. The data analysis method for this research is the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) using the SPSS version 26 program. The results of the research show that the level of customer satisfaction (CSI) with service quality is 77.60% in the satisfied category. Meanwhile, the level of customer satisfaction (CSI) regarding price was 79.01%. This means that customers are satisfied with the quality of service and prices offered by PT. Gustaman Express Pekanbaru. In the service quality variable, there are 7 items in the main quadrant, namely modern equipment, cleanliness of physical facilities, facilities that are visually attractive, informing about certainty of service times, providing services according to promises, delivering services correctly the first time, delivering services in accordance with promised time. Meanwhile, in the price variable, there is 1 item that is in the main quadrant, namely competitive prices. This means that these items are considered important for customers, but the company's performance is still low, so improvements are needed in the future. Keywords: Customer Satisfaction, Service Quality, Price